COVID-19 Infection With the Omicron SARS-CoV-2 Variant in a Cohort of Kidney and Kidney Pancreas Transplant Recipients: Clinical Features, Risk Factors, and Outcomes. Issue 9 (19th August 2022) - Wong, Germaine; Rowlandson, Matthew; Sabanayagam, Dharshana; Ginn, Andrew N.; Kable, Kathy; Sciberras, Frederika; Au, Eric; Draper, Jenny; Arnott, Alicia; Sintchenko, Vitali; Dwyer, Dominic E.; Chen, Sharon C.A.; et al.
Abstract : Background: Since November 2021, a new variant of concern (VOC), the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) lineage B.1.1.529 (Omicron) has emerged as the dominant coronavirus disease 2019 (COVID-19) infection worldwide. We describe the clinical presentation, risk factors, and outcomes in a cohort of kidney and kidney pancreas transplant recipients with COVID-19 caused by Omicron infection. Methods: We included all kidney and kidney pancreas transplant recipients diagnosed with SARS-CoV-2 Omicron infections between December 26, 2021, and January 14, 2022, in a single transplant center in Australia. Identification of the VOC Omicron was confirmed using phylogenetic analysis of SARS-CoV-2 sequences. Results: Forty-one patients with kidney (6 living and 33 deceased) and kidney pancreas transplants were diagnosed with the VOC Omicron (lineage B.1.1.529/BA.1) infection during the study period. The mean age (SD) at the time of diagnosis was 52 (11.1) y; 40 (out of 41) (98%) had received at least 2 doses of COVID-19 vaccine. Cough was the most frequent symptom (80.5%), followed by myalgia (70.7%), sore throat (63.4%), and fever (58.5%). After a follow-up time of 30 d, 1 (2.4%) patient died, 2 (4.9%) experienced multiorgan failure, and 5 (12.2%) had respiratory failure; 11 (26.8%) patients developed other superimposed infections. Compared with recipients who did not receive sotrovimab antibody therapy, the odds ratio (95% confidence interval) for hospitalization among patients who received sotrovimab was 0.05 (0.005-0.4). Conclusions: Despite double or triple dose vaccination, VOC Omicron infections in kidney and kidney pancreas transplant recipients are not necessarily mild. Hospitalization rates remained high (around 56%), and sotrovimab use may prevent hospitalization. Abstract :